Genitale Blutung im Vorschulalter: der Urethralprolaps als interdisziplinäre Herausforderung = Genital bleeding in a pre-schooler : urethral prolapse as an interdisciplinary challenge - Wegele, Christian; Stein, Raimund; Dürken, Matthias; Bussen, Stefanie; Karremann, Michael (Monatsschrift Kinderheilkunde, 2018)
This article presents the case of a 4-year-old girl with a painless, bleeding tumor on the genitals. Genital bleeding in prepubertal girls is a red flag. Reasons for bleeding at this age are manifold. In addition to a benign origin, the possibility of physical abuse by a third party must be excluded, but a rare diagnosis such as a urethral prolapse should not be discounted. The diagnosis is usually clinical and can be treated conservatively in most cases.
First Online: 27 April 2017
Gesehen am 01.07.2019